Can genius be taught? Debates in Portuguese music education (1868–1930). (July 2017) - Paz, Ana Luísa Fernandes
This paper examines how the idea of musical genius, a mythical notion used as a device for musical practices, facilitates a split between the genius of an innate learner and that of an apprentice, thus creating an ambiguous discursive space. Genius was firstly a matter of nature, but also most discussed under the topic of nurture, that is, education. In order to understand how this nature and nurture ambiguousness developed in specific terms for the musical genius I focussed on analysing historical documents on the main resources for genius-building. In this article, these resources are considered the raw material for the embodying of the genius in every single person. What I discovered about the term 'genius' and its contradictory uses to support both elitist and democratic schooling made me realise that it is treated as an argument to advocate the merits of music and to take concrete steps in implementing educational excellence. The term 'genius' can serve any pedagogical purpose and encompass contradictory ideas, potentially serving unlimited purposes. Genius can be applied to the best of students, but equally to virtually anyone. In future studies the question will be whether this reading fits the scenario in other European countries.